EFFECT OF TWO DIFFERENT PERMEABLE CRYOPROTECTANTS ON FREEZABILITY OF EXOTIC STALLION AND JACK SEMEN - TALLURI, T R; RAVI, S K; SINGH, C; LEGHA, R A; MEHTA, s c; PRAKASH, V; TRIPATHI, B N (The Indian Journal of Animal Reproduction, 2022)
Semen was collected from the exotic stallions and exotic jacks (n=5 each) using an artificial vagina. Thefresh semen was treated with primary extender and centrifuged to remove seminal plasma. Sperm pelletobtained after centrifugation was equally divided to receive secondary extender containing same amount (5%)of different permeable cryoprotectants, either glycerol (Gly) or dimethyl formamide (DMF) before submitting forcryopreservation. Various sperm parameters were assessed at pre-freeze and post-thaw stage which revealeddifferences (p
Keywords: Cryopreservation; Di-Methyl Formamide; Glycerol; Jack; Semen; Stallion